2020
DOI: 10.1186/s12903-020-01106-6
|View full text |Cite
|
Sign up to set email alerts
|

Cone beam computed tomography (CBCT) in periodontal diseases: a Systematic review based on the efficacy model

Abstract: Background: Periodontal diseases are prevalent among adult populations. Its diagnosis depends mainly on clinical findings supported by radiographic examinations. In previous decades, cone beam computed tomography has been introduced to the dental field. The aim of this study was to address the diagnostic efficacy of cone-beam computed tomographic (CBCT) imaging in periodontics based on a systematic search and analysis of the literature using the hierarchical efficacy model. Methods: A systematic search of elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…However, in a more recent literature review, it was found that there is an increase in the available evidence supporting the use of CBCT in the management of periodontal disease, especially in preoperative planning and follow-up of regenerative surgical treatment, even though it is not recommended as a standard of care [ 38 ]. In a systematic review on the use of CBCT in periodontal disease, it was found to be accurate in the management of both infrabony defects and furcation lesions [ 39 ]. It can also be justifiable to use CBCT when assessing periodontal diseases around complex structures like maxillary molars [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in a more recent literature review, it was found that there is an increase in the available evidence supporting the use of CBCT in the management of periodontal disease, especially in preoperative planning and follow-up of regenerative surgical treatment, even though it is not recommended as a standard of care [ 38 ]. In a systematic review on the use of CBCT in periodontal disease, it was found to be accurate in the management of both infrabony defects and furcation lesions [ 39 ]. It can also be justifiable to use CBCT when assessing periodontal diseases around complex structures like maxillary molars [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBCT was found to be beneficial and accurate in cases of infrabony defects and furcation involvements. (59) The image acquisition was performed using i-CAT next generation (Imaging sciences international, Hatfield, PA, USA) with exposure parameters 120 kVp, 5 mA, 0.2 mm voxel size, 26 seconds scanning time and field of view was limited to the mandibular arch (5 X 10 cm). The radiographic scanning was repeated six months after the surgery using the same parameters.…”
Section: Radiographic Evaluationmentioning
confidence: 99%
“…The realistically achievable spatial resolution for images offering no visible blurring or moving artefacts is about 0.25-0.5 mm in-vivo [29]. Nevertheless, CBCT analysis is a reliable diagnostic tool for assessing bone level, and thus also allows appropriate periodontal treatment planning, as actual bone level correlates with the clinical situation well [15,17,30,31]. Even its suitability for assessing the cemento-enamel junction of teeth under clinical conditions has been proven [32].…”
Section: Cbct-analysismentioning
confidence: 99%